2012
DOI: 10.1100/2012/269476
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Lycosome Formulation Improves Vascular Functions and Plasma Lipids with Reduction of Markers of Inflammation and Oxidative Stress in Prehypertension

Abstract: Parameters reflecting cardiovascular health and inflammation were studied in a pilot clinical trial conducted on 40 patients with prehypertension. The patients were treated with a new proprietary formulation of a whey protein (WP) isolate embedded into lycopene micelles (WPL) during a 1-month period. Control groups received lycopene or WP as a singular formulation or placebo pills for the same period of time. Combined WPL formulation of whey protein and lycopene has caused multiple favorable changes in the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
(27 reference statements)
1
34
0
Order By: Relevance
“…Lycosome formulation of lycopene containing a phospholipid chaperone may provide a significant level of protection for "cargo" lycopene molecules from stomach acidity and digestive enzymes. In our previous work, we demonstrated that this protection resulted in an enhanced bioavailability rate and efficacy for a number of nutraceutical molecules such as resveratrol, whey protein peptides, cocoa flavanols, and certain pharmaceuticals (Bashmakov et al, 2014;Petyaev, 2015;Petyaev, Dovgalevsky, Chalyk, Klochkov, & Kyle, 2014;Petyaev, Dovgalevsky, Klochkov, Chalyk, & Kyle, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Lycosome formulation of lycopene containing a phospholipid chaperone may provide a significant level of protection for "cargo" lycopene molecules from stomach acidity and digestive enzymes. In our previous work, we demonstrated that this protection resulted in an enhanced bioavailability rate and efficacy for a number of nutraceutical molecules such as resveratrol, whey protein peptides, cocoa flavanols, and certain pharmaceuticals (Bashmakov et al, 2014;Petyaev, 2015;Petyaev, Dovgalevsky, Chalyk, Klochkov, & Kyle, 2014;Petyaev, Dovgalevsky, Klochkov, Chalyk, & Kyle, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recently the lycosome microencapsulation technology was successfully applied for other hydrophobic nutraceuticals with poor absorption rate — resveratrol, whey protein peptides (Petyaev et al. ; Bashmakov et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The rat study of Tong et al (112) using a high-fat diet showed that whey protein significantly increased HDL-cholesterol although this has not been consistently shown in human studies (113) . Some studies have shown whey protein to have a tendency to reduce plasma TAG (114) and total cholesterol (115) and a meta-analysis on the effect of whey protein on blood lipids would be valuable. A recent study (116) showed that compared with whey protein, casein markedly reduced postprandial TAG (22 (SD 10) % reduction in the 6 h AUC; P < 0·05).…”
Section: Dairy Proteins and Blood Lipidsmentioning
confidence: 99%